Adverse drug reactions to herbal medicines. (December 2021) - Routledge, Philip A.; Bracchi, Robert
Abstract : Summary: Herbal medicines may cause adverse drug reactions (ADRs) due to effects of known constituent(s), substitution with other herbal ingredients, or contamination or adulteration with additional substances. Healthcare professionals (HCPs) should always take a full medicines history, including use of herbal medicines and other complementary products (e.g., food supplements and other dietary supplements). A range of resources are available to inform HCPs and the public/patients/ carers about possible ADRs associated with herbal medicines. HCPs and the public/patients also need to be made aware of the importance of reporting suspected ADRs to the appropriate regulatory agency. Good safety surveillance systems can thus help to ensure that those who choose to take herbal medicines are able to do so with acceptable safety.